Early hypervigilance and later avoidance: Event-related potentials track the processing of threatening stimuli in anxiety. (November 2022) - Kausche, Franziska Magdalena; Härpfer, Kai; Carsten, Hannes Per; Kathmann, Norbert; Riesel, Anja
Abstract: Avoidance behavior is a core symptom of anxiety disorders that may hinder adaptation. Anxiety disorders are heterogeneous and previous research suggests to decompose anxiety into two dimensions: anxious apprehension and anxious arousal. How these two dimensions are associated with avoidance of and exposure to threatening stimuli, as well as their accompanying neural processes, is barely understood. We examined threat processing using event-related potentials (N1, LPP) from 134 individuals considering the influence of anxiety dimensions. During a two-phase picture-viewing task the participants watched neutral and threatening pictures, which they were instructed to either avoid or attend to during repeated presentations. Results showed that threatening compared to neutral pictures were associated with increased attention allocation (N1) and in-depth processing (LPP), modulated by task-instructions (lower during avoidance). Further, increased anxious apprehension was associated with heightened automatic attention (increased N1), followed by reduced LPP amplitudes for threatening pictures suggesting reduced in-depth processing. During re-exposure, threatening pictures were associated with increased in-depth processing, with no difference between previously avoided and maintained pictures. Together, these results illustrate that avoidance and high anxious apprehension seem to lead to similar neural changes in the processing of aversive images that may conflict with long-term adaptation. Highlights: Threat is associated with increased automatic and in-depth processing. High levels of worry lead to reduced in-depth processing of threat during habituation. Instructed avoidance decreases in-depth processing of threat during habituation. During re-exposure, previous avoidance results in increased in-depth processing. To increase responding, exposure therapy should be tailored to individual worry.